Рыба. История одной миграции: роман / П. М. Алешковский - Алешковский Петр Маркович (Самое время, 2009)
Экземпляры: Аб.,3,5,7,9ф-лы (20.01.2012г.) / Инвентарный номер: 46649 / Цена: / Сис.шифр: Р2 / Авт.знак: А49 / ББК: Р2